2006
DOI: 10.1152/ajpregu.00047.2006
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic mediation of constant light-potentiated nonphotic phase shifting of the circadian locomotor activity rhythm in Syrian hamsters

Abstract: (1-3 days) constant light exposure (brief LL) potentiates nonphotic phase shifting induced by sleep deprivation and serotonin (5-HT) agonist stimulation. The present assessments reveal that exposure to brief LL markedly alters the magnitude and shape of the 5-HT 1A,7 receptor agonist, 8-(ϩ)2-dipropyl-amino-8-hydroxyl-1,2,3,4-tetrahyronapthalene (8-OH-DPAT) phase-response curve, facilitating (ϳ12 h) phase-advance shifts during the early morning when serotonergics have no phase-shifting effect. Brief LL also red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…5). Similar responses to other non-photic phase-shifting stimuli have been reported recently in animals pre-exposed to constant light for one or more cycles prior to phase-shift testing (Knoch et al, 2004(Knoch et al, , 2006Landry and Mistlberger, 2005). Thus, these responses may have been related to our decision to delay the onset of darkness from the normal ZT 12 until ZT 21 on the day of treatment in order to facilitate triazolam administration during the night phase of the LD cycle, resulting in exposure to 23 hours of continuous light.…”
Section: Triazolam-induced Phase Responsessupporting
confidence: 78%
See 1 more Smart Citation
“…5). Similar responses to other non-photic phase-shifting stimuli have been reported recently in animals pre-exposed to constant light for one or more cycles prior to phase-shift testing (Knoch et al, 2004(Knoch et al, , 2006Landry and Mistlberger, 2005). Thus, these responses may have been related to our decision to delay the onset of darkness from the normal ZT 12 until ZT 21 on the day of treatment in order to facilitate triazolam administration during the night phase of the LD cycle, resulting in exposure to 23 hours of continuous light.…”
Section: Triazolam-induced Phase Responsessupporting
confidence: 78%
“…We chose the latter strategy, both to equate lighting conditions for the ZT 6 and ZT 21 injections, and for experimental convenience. However, recent studies have shown that pre-exposure to even relatively short periods of continuous light (i.e., 1−3 circadian cycles) can dramatically potentiate the response to other varieties of non-photic stimuli (Knoch et al, 2004(Knoch et al, ,2006Landry and Mistlberger, 2005). Thus, these observations suggest that similar light-induced potentiation of non-photic phase responses may also occur for triazolam-induced responses in some animals.…”
Section: Discussionmentioning
confidence: 94%
“…It has been reported that systemic administration of 8-OH-DPAT causes a large non-photic phase shift in behavioral activity by activating 5-HT 1A receptors on the SCN when exposed to short-term constant light (15). This phase-shifting is associated with the decreased 5-HT release in the SCN and is not blocked by 5-HT 7 receptor antagonists.…”
Section: Short Communicationmentioning
confidence: 99%
“…One possibility is that 5-HT receptor numbers are altered by brief LL, such that postsynaptic responses are enhanced and/or presynaptic autoinhibitory responses are attenuated. However, autoradiographic analyses of 8-OH-DPAT binding in the SCN and midbrain raphe have provided no evidence for upregulation or downregulation of 5-HT receptors by brief LL (11,22). Changes at the level of second messengers remain possible, but there could be a more general mechanism at work.…”
mentioning
confidence: 99%
“…In this issue of the American Journal of Physiology-Regulatory, Integrative and Comparative Physiology, Knoch et al (22) report their third in a recent series of studies in which they describe and pharmacologically characterize a marked potentiation of nonphotic phase shifting in Syrian hamsters by one or two nights of exposure to constant light (brief LL). The inspiration for testing this effect of light was empirically grounded, as follows.…”
mentioning
confidence: 99%